Penerapan Teknologi Mesin Pencacah Rumput untuk Kelompok At Taqwa Farm di Desa Sekura - Nopriandy, Feby; Suhendra, Suhendra; Anjiu, Leo Dedy; Rianto, Ari (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2024)
The partner in this program is the At Taqwa Farm group, Sekura Village. The focus of the At Taqwa Farm group is agriculture and animal husbandry. This group has been established since 2020, and has 55 goat farming. The main problem faced by partners is in the feeding process. So far, partners have provided food by taking grass or leaves with a scythe, then simply giving it to livestock. Based on the partner's problems, the service implementation team provided a solution in the form of applying technology using an animal feed chopper machine to the partners. The stages of service activities include chopping machine design, chopping machine manufacturing, chopping machine performance testing, training on operation and maintenance of chopping machines, as well as handing over chopping machines to partners. The grass chopper machine handed over to the partner can function well in chopping grass for animal feed. This really helps partners increase their grass chopping capacity, making the feed preparation process easier for partners.